RapidMiner : data mining use cases and business analytics applications - Hofmann, Markus (Computer scientist); Klinkenberg, Ralf (Chapman & Hall/CRC data mining and knowledge discovery series ;, 2014)
"RapidMiner is one of the most widely used open source data mining solutions world-wide. This book provides an application use case-based introduction to data mining and to RapidMiner (and RapidAnalytics.) It presents many different applications of data mining and how to implement them with RapidMiner, and it allows readers to get started with their own data mining applications with RapidMiner, or other similar tools. The software, the data sets, and RapidMiner data mining processes used and discussed in the book are made available to readers"--